Insulinoma management in a geriatric local dog - Leong, Z. P.; Watanabe, M. (Veterinary Association Malaysia, 2014)
A 14-year-old, spayed female local dog was presented to University Veterinary Hospital-University Putra Malaysia (UVH-UPM) for the complaint of uncontrollable seizures. The intracranial neoplasia or trauma as a cause of seizures was ruled out based on magnetic resonance imaging conducted prior to presentation. Full diagnostic investigation inclusive of haematology, serum biochemistry, parasitology, thoracic and abdominal radiography and abdominal ultrasonography was conducted. A diagnosis of insulinoma was made from the persistent, low fasting blood glucose levels and the inappropriately high fasting insulin level, as well as the response to treatment with prednisolone